2023
DOI: 10.5812/semj-137241
|View full text |Cite
|
Sign up to set email alerts
|

Digital Cognitive Tests for Dementia Screening: A Systematic Review

Abstract: Context: The number of people with dementia is increasing dramatically. With the outbreak of the COVID-19 pandemic, digital screening tests can play a significant role in the remote and timely detection of people with dementia. This study aimed to review digital cognitive tests for dementia screening. Methods: We searched Web of Science, ProQuest, PubMed, Scopus, and Cochrane using related terms such as “dementia,” “mobile,” “digital,” “computer,” and “cognitive assessment,” leading to the emergence of 1,348 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Generally, in order to monitor disease progression in different domains each patient is examined with several tests and on a regular basis, so their times add up and become large in the long run. An approach to diminish the administration, scoring, interpretation, and documentation times of neuropsychological tests is the usage of computerized or digital cognitive tests [ 86 ]. In that recent systematic review those authors found out that almost 60% were mobile-based screening tests; near 3 out of 10, desktop-based; and the rest, web-based.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, in order to monitor disease progression in different domains each patient is examined with several tests and on a regular basis, so their times add up and become large in the long run. An approach to diminish the administration, scoring, interpretation, and documentation times of neuropsychological tests is the usage of computerized or digital cognitive tests [ 86 ]. In that recent systematic review those authors found out that almost 60% were mobile-based screening tests; near 3 out of 10, desktop-based; and the rest, web-based.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, these digital versions ease remote and self-administration. However, due to the different way the neuropsychological test is conducted, results for the paper and digital versions of the same test may differ [ 86 ].…”
Section: Methodsmentioning
confidence: 99%